2002
DOI: 10.1007/s00415-002-0745-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the COL3A1 gene in patients with spontaneous cervical artery dissections

Abstract: The etiology of spontaneous cervical artery dissection (sCAD) is unknown. An underlying connective tissue disorder has been suggested. As a collagen disease is conceivable several genes encoding fibrillar collagens have been condsidered as candidate genes for sCAD. We analysed the COL3A1 gene in patients with spontaneous cervical artery dissection (sCAD) and in healthy controls, using three different genetic methods. 1) The promoter region, the 5' and 3' untranscribed regions and the N- and C- peptide encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Five studies reported associations with 3 different candidate genes: ICAM-1, COL3A1, and MTHFR. 8,9,12,51,66 The associations with the ICAM-1 E469K polymorphism and the COL3A1 3ЈUTR 2-bp deletion, 12,51 observed in 2 relatively small studies, have not been replicated and should therefore be interpreted with caution. The ICAM-1 E469K polymorphism could modify the affinity of ICAM-1 to its ligands, which may lead to increased activation of cytokines and proteases, thus inducing extracellular matrix degradation and weakening of the arterial wall.…”
Section: Genetic Association Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies reported associations with 3 different candidate genes: ICAM-1, COL3A1, and MTHFR. 8,9,12,51,66 The associations with the ICAM-1 E469K polymorphism and the COL3A1 3ЈUTR 2-bp deletion, 12,51 observed in 2 relatively small studies, have not been replicated and should therefore be interpreted with caution. The ICAM-1 E469K polymorphism could modify the affinity of ICAM-1 to its ligands, which may lead to increased activation of cytokines and proteases, thus inducing extracellular matrix degradation and weakening of the arterial wall.…”
Section: Genetic Association Studiesmentioning
confidence: 99%
“…One linkage analysis was performed in a family with 3 members affected by CAD using CA repeat markers that flank the COL3A1 locus yielding negative results. 51 Other linkage studies have been performed in families with only one member affected by CAD but several members presenting dermal connective tissue aberrations (intermediate phenotype)…”
Section: Linkage Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34]39,47,48 None of the identified mutations, however, was suggested to play a major role in the cause of CAD.…”
Section: Gene Mutation/sequencing Studiesmentioning
confidence: 99%
“…We did not attempt genetic analysis because the results in several studies investigating genes causing CTD were negative in patients with SCAD. 2,9 The data on EDS IV suggest that despite following an autosomal-dominant trait, phenotype and age of presentation can vary considerably. 3 New mutations may occur in up to 50%.…”
Section: Resultsmentioning
confidence: 99%